Giant gastrointestinal stromal tumor of ileum: the gist of GIST: a case report - Ray, M. S.; Deepak, B. S. (International Surgery Journal, 2017)
Gastrointestinal stromal tumors (GIST) are relatively rare pathology as compared with other mitotic lesions of GIT. However, GIST is the most common mesenchymal neoplasms of the gastrointestinal tract. Biopsy of the lesion and Immuno-Histo-Chemistry (IHC) for CD117 confirms the diagnosis. Surgery remains the standard of care and only potentially curative therapy for patients with primary, resectable, localized gastrointestinal stromal tumor. However, chemotherapy with Imatinib is added in neoadjuvant or adjuvant form according to clinical situation, and histopathological status of the lesion.